The macrophage mannose receptor - Martinez-Pomares, Luisa (Henry Stewart Talks, 2012)
The mannose receptor (MR), Structure and function, Domains and binding properties of MR, The MR family, MR expression, MR as an endocytic receptor, MR conformation and glycosylation, MR and phagocytosis, MR and cellular activation, MR shedding, Ligands for the cysteine-rich domain of MR, MR and antigen presentation, MR and self-recognition, MR and activation of T cells, MR and disease, Role of MR in host defence, MR and allergy, MR and glomerulonephritis, MR and cancer